Morphology of bolsonarism: affection and identity in the constitution of an imagined ultra-right community - Roman, Artur Roberto (The ESPecialist, 2025)
The general objective of this article is to bring reflections that contribute to understanding the political and social phenomenon called “bolsonarismo”, as an expression of the ultra-right (far right) in Brazil (Mudde, 2021). The specific objective is to discuss the dynamics of social constitution of bolsonarismo, its ideological configuration and conceptual structure, process modeled and manipulated to meet the interests of Brazil's economic oligarchy. The hypothesis of this article is that the constitution of bolsonarismo was promoted and facilitated by Bolsonaro's ability to produce discourses that mobilize affection that trigger identification among his followers (Mouffe, 2007) and stimulate antagonism between militants and supporters of opposing political camps (Mouffe, 2018), integrating their followers into an imagined community (Anderson, 2008). The article concludes by highlighting the role of the university in the task of ensuring the achievements of the Democratic Rule of Law, maintaining o bolsonarismo within civilizing limits, with the use of republican mechanisms and legal safeguards.